Homogenous implant in rat tibias of matrix preserved in 98% glycerin: histomorphologic study. - Okamoto, Tetuo [UNESP]; Kira, Marcos Eduardo [UNESP]; Okamoto, Roberta [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Niccoli Filho, Walter Domingos [UNESP] (My University, 2000)
As a chemical medium for preservation of tissues, glycerin has shown good results because it maintains the cellular integrity despite the tissue dehydration it causes. Taking advantage of the osteoinducing properties of the osseous matrix and glycerin as a proper medium for tissue preservation, osseous matrix was implanted in rat tibias. Twenty-four rats were used, each receiving two surgical wounds. In one of the wounds an osseous matrix preserved in 98% glycerin was implanted and the other received a matrix without preservatives. Six animals were sacrificed on days 10, 20, 30 and 60 post-implant. After routine histological processing, the specimens were stained in hematoxylin-eosin and Masson's trichrome. The results showed that the matrixes preserved in glycerin presented faster resorption with replacement by newly formed tissue.
Keywords: azo compound; collagen; coloring agent; diagnostic agent; eosin; fluorescent dye; glycerol; hematoxylin; methyl green; preservative; allotransplantation; animal; bone development; bone matrix; connective tissue; fibroblast; follow up; male; osteoblast; osteolysis; pathology; physiology; rat; tibia; tissue preservation; transplantation; trichrome stain; Wistar rat; Animals; Azo Compounds; Bone Matrix; Bone Resorption; Collagen; Coloring Agents; Connective Tissue; Eosine Yellowish-(YS); Fibroblasts; Fluorescent Dyes; Follow-Up Studies; Glycerol; Hematoxylin; Male; Methyl Green; Osteoblasts; Osteogenesis; Preservatives, Pharmaceutical; Rats; Rats, Wistar; Tibia; Tissue Preservation; Transplantation, Homologous